Feasibility of Same-Day Discharge After Laparoscopic Roux-en-Y Gastric Bypass Using Remote Monitoring - Nijland, Leontien M.G. (Obes Surg, 2021)
BACKGROUND: Shortening of hospital stay to 1 night has not affected the short-term safety of patients undergoing laparoscopic Roux-en-Y gastric bypass (RYGB). Whether the RYGB is feasible in an ambulatory setting (same-day discharge) without overnight hospital stay remains to be answered. We aimed to evaluate the feasibility of same-day discharge after laparoscopic Roux-en-Y gastric bypass (RYGB) using additional live video consultation and remote monitoring. Same-day discharge (SDD) was defined as surgery without postoperative overnight hospital stay. METHODS: This was a single-center prospective feasibility study in a selected group of patients undergoing a RYGB. Fifty patients undergoing a primary RYGB were selected and potentially treated following the SDD protocol. After SDD discharge patients were remotely monitored after surgery for 48 h using a medical device measuring vital signs three times a day. Video consultations were performed by a doctor twice a day for 2 postoperative days. Primary outcome was the success rate (%) of SDD. Secondary outcomes were emergency room presentations, readmissions, early complications (<30 days), and patient satisfaction. RESULTS: A total of 50 patients were selected for the SDD treatment protocol between June 2020 and November 2020. An SDD success rate of 88 % (44/50 patients) was achieved. Five patients (10%) presented at the emergency room, 2 of whom (4%) were readmitted because of a complication within 30 days after surgery. Overall, patients who followed the SDD protocol reported high satisfaction scores. CONCLUSION: A RYGB with SDD can be considered feasible using remote monitoring for a selected group of patients. GRAPHICAL ABSTRACT: [Image: see text]